Energy transition in the enhancement and break of turbulence barrier during heavy haze pollution. (15th January 2023) - Ren, Yan; Zhang, Hongsheng; Wu, Bingui; Zhang, Lei; Liang, Jiening; Zhang, Xiaoye
Abstract: Variation of the turbulence barrier effect caused by the turbulence intermittency have a strong impact on the vertical distribution and variation of pollutants, which limits the accuracy of pollution process simulation. Turbulence observation data from the five layers of the 255 m meteorological tower in Tianjin during two severe haze pollution periods were used to discuss energy changes during the enhancement and break of the turbulence barrier. Results showed that a sharp decrease in turbulence kinetic energy contributed to barrier enhancement and the kinetic energy transfer from sub-mesoscale motion to turbulence triggered the barrier break. The barrier break point tends to occur after Δ KE < 0 (the kinetic energy difference between turbulence and sub-mesoscale motion), subsequently followed by a significant increase in Δ KE. Due to the significant reduction in wind speed during severe haze pollution, type-B intermittency events occurred more frequently and existed at five heights. Type-A intermittency events were more likely to occur at the heights of 40 and 80 m, and type-C intermittency events were more likely to occur at heights above 80 m. Wind speed thresholds at different heights (2.5 m s −1 for 40 m, 4 m s −1 for 80 m, 4 m s −1 for 120 m, 4 m s −1 for 160 m, 4.5 m s −1 for 200 m) can be used to determine whether turbulent barrier effects occurred. This study provides an important research basis for solving the theoretical problem of the stable boundary layer that currently limits the accurate prediction of severe haze pollution processes. Graphical abstract: Image 1 Highlights: The sharp decrease of turbulence kinetic energy contributes to barrier enhancement. Energy transition from sub-mesoscale to turbulent motion triggers barrier break. Barrier break point tends to occur after Δ KE < 0 following significant increase. Type-B intermittency occurs more frequently and exists at all levels in haze events. Wind speed thresholds for whether turbulence barrier effect occur was determined.